2017
DOI: 10.1093/ntr/ntx234
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and Aldehyde Content in Flavored Electronic Cigarette Liquids

Abstract: The data can inform the regulation of specific flavor constituents in tobacco products as a strategy to protect young people from using e-cigarettes, while balancing FDA's interest in how these emerging products could potentially benefit adult smokers who are seeking to safely quit cigarette smoking. The data can also be used to educate consumers about ingredients in products that may contain nicotine and inform future FDA regulatory policies related to product standards and accurate and comprehensible labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…As mentioned earlier, recent studies have shown that these compounds degrade into aldehydes when heated, however, to a much lesser extent than certain flavourings. These studies have also found aldehydes in unheated e‐liquids 15 . One study conducted on rats determined that PG and VG aerosols showed limited biological effects and limited toxicity, whereas PG and VG with nicotine aerosols resulted in toxic lung and metabolic effects 67 …”
Section: Toxicological Effects Of E‐cigarettesmentioning
confidence: 98%
See 2 more Smart Citations
“…As mentioned earlier, recent studies have shown that these compounds degrade into aldehydes when heated, however, to a much lesser extent than certain flavourings. These studies have also found aldehydes in unheated e‐liquids 15 . One study conducted on rats determined that PG and VG aerosols showed limited biological effects and limited toxicity, whereas PG and VG with nicotine aerosols resulted in toxic lung and metabolic effects 67 …”
Section: Toxicological Effects Of E‐cigarettesmentioning
confidence: 98%
“…There are no medicinally licensed nicotine vaping products in the United Kingdom. In 2016, the FDA declared that ECs and flavoured e‐cigarette liquids are tobacco products and are therefore subject to regulation that governs their manufacturing, marketing and distribution 15 …”
Section: Laws and Levels Around The Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that other sources than PG and G contribute to a major extent to the formation of AA. Sugars and flavors were recently discussed as possible sources for carbonyl emissions in EC aerosols (Fagan et al 2018;Khlystov and Samburova 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While complete substitution of ECs for cigarettes has been associated with smoking cessation [6, 7], concomitant or “dual” use of ECs and cigarettes has not [8], and dual use is now the most common form of EC use [9]. Further, dual use has not been shown to reduce exposure to the harmful products of combustible cigarettes, including carcinogens [1018]. The American Cancer Society, as a result, strongly discourages the dual use of EC and cigarettes [19].…”
Section: Introductionmentioning
confidence: 99%